Multi-Physical Field Coupling Simulation of Φ100 Cold Crucible-Glass Solidification High Frequency Power Supply - WANG Zexue;LI Yusong;ZHU Dongdong;ZHANG Anqi;HONG Ye;LONG Haoqi;ZHANG Shengdong (Yuanzineng kexue jishu, 2023)
High-frequency power supply is an important component of high-discharge glass curing systems for high level radioactive waste (HLLW) of cold crucibles, but because the parameters of each set of high-frequency power supply are not adjustable from the factory and are expensive, it is impossible to study the matching of the power supply parameters to the cold crucible and determine the optimal combination of parameters and the best matching state for the high-frequency power supply. The use of a small, inexpensive and fine-tunable high-frequency power supply to set up a Φ100 cold crucible experimental setup and to investigate the match between the power supply and the crucible is an effective way to solve this problem, but due to the large number of experimental variables and the small amount of valid data available from actual measurements, it is decided to carry out a simulation study of the multi-physics field coupling of a Φ100 cold crucible glass-curing high-frequency power supply. In this paper, COMSOL was used to carry out a multi-physical field coupling simulation of the temperature, flow and magnetic fields of the molten glass liquid, using current strength, frequency and number of turns of the coil as variables. The results show that increasing the current strength and frequency improves the melting capacity, increasing the coil diameter, spacing and number of turns improves the energy utilisation, the coil height is lower in the middle to improve the temperature field and magnetic field distribution, and the round coil and cold crucible are more advantageous than the oval. The initial optimization of the power supply parameters results in a 22.8% increase in the melt cell volume and a 35% increase in the average temperature of the cold crucible, which significantly improves the melting effect of the cold crucible. The simulated experiments provide guidance for the development of the Φ100 cold crucible experiments and lay the foundation for the optimisation of the high frequency power supply and coil parameters.